Quality of life among the Penan community at Murum Resettlement site MRS, Belaga Sarawak - Ambau, Modin; Zaki, Pakhriazad Hassan; Emang, Diana; Magiman, Mohammad Maulana (Persatuan Penyelidik Latihan Kemahiran Dan Vokasional (ARSVOT), 2022)
The main goal of development in a country is to provide a better quality of life for all levels of society. A quality life is determined by several factors, such as home ownership, safety, health, education, amenities and many more. All these affect people’s well-being and satisfaction in life. It is the same for the Penan community at Murum Resettlement Site (MRS) in Belaga District, Sarawak which is affected by the construction of the Murum Dam. The relocation of the Penans to MRS was to ensure they have a better life because the resettlement area is provided with all kinds of facilities and infrastructure. After almost eight years, there has been no study on the quality of life of the relocated Penans at this resettlement area Therefore, this study was conducted to examine the quality of life of the affected Penans at MRS. This study was conducted from December 2020 to February 2021 at MRS using quantitative and qualitative approaches. Data were collected using questionnaires, in-depth interviews and field observations. A total number of 269 household heads and six key informants were interviewed. SPSS software was used to analyze the data collected. The findings indicated that there were positive changes in the quality of life of those who were affected. However, elements such as education, health, road system and land compensation still need to be looked into and improved. Their views and involvement in development programmes should be enhanced. Overall, the construction of Murum Dam that caused resettlement of the Penans managed to improve their quality of life.